RULES PROPOSED TO CURB SMOKING IN FEDERAL OFFICES (Tufts Archival Research Center, 2007)
Article reporting the new government regulations which would restrict smoking in government buildings. Cites the irritation of secondhand smoke to those with asthma and heart disease as a primary reason.